2011
DOI: 10.1242/dev.056903
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-A controls mesoderm cell orientation and radial intercalation duringXenopusgastrulation

Abstract: Radial intercalation is a common, yet poorly understood, morphogenetic process in the developing embryo. By analyzing cell rearrangement in the prechordal mesoderm during Xenopus gastrulation, we have identified a mechanism for radial intercalation. It involves cell orientation in response to a long-range signal mediated by platelet-derived growth factor (PDGF-A) and directional intercellular migration. When PDGF-A signaling is inhibited, prechordal mesoderm cells fail to orient towards the ectoderm, the endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 43 publications
3
78
0
1
Order By: Relevance
“…As pdgf-b mRNA is extremely poorly expressed during gastrulation, this data corroborates the idea that in the early phases of development, the main role of PDGF signalling is played by the homodimer pdgf-aa via pdgfr-a. This is in line with the observation that in pdgf-a morphants the prechordal mesoderm fails to spread during gastrulation and no compensatory mechanisms occurs (Damm and Winklbauer, 2011). At the end of neurulation (Stage 20), pdgf-b mRNA expression level rose and then decreased again at late tailbud stages (stage 35) (Fig.…”
Section: Pdgf-b Is Expressed During Xenopus Laevis Developmentsupporting
confidence: 89%
See 1 more Smart Citation
“…As pdgf-b mRNA is extremely poorly expressed during gastrulation, this data corroborates the idea that in the early phases of development, the main role of PDGF signalling is played by the homodimer pdgf-aa via pdgfr-a. This is in line with the observation that in pdgf-a morphants the prechordal mesoderm fails to spread during gastrulation and no compensatory mechanisms occurs (Damm and Winklbauer, 2011). At the end of neurulation (Stage 20), pdgf-b mRNA expression level rose and then decreased again at late tailbud stages (stage 35) (Fig.…”
Section: Pdgf-b Is Expressed During Xenopus Laevis Developmentsupporting
confidence: 89%
“…After the start of the zygotic transcription (stage 8), pdgf-b mRNA was barely detectable and it showed a low expression level both during gastrulation (stage 10.5) and neurulation (stage 13); on the contrary, pdgfr-a was abundantly expressed at these stages. During gastrulation in Xenopus, a crucial role for pdgf-a and pdgfr-a has been demonstrated (Damm and Winklbauer, 2011). As pdgf-b mRNA is extremely poorly expressed during gastrulation, this data corroborates the idea that in the early phases of development, the main role of PDGF signalling is played by the homodimer pdgf-aa via pdgfr-a.…”
Section: Pdgf-b Is Expressed During Xenopus Laevis Developmentsupporting
confidence: 79%
“…In several organisms, it has been shown that a single growth factor influences multiple cell behaviors, although the details vary. During Xenopus gastrulation, PDGF regulates the orientation, radial intercalation and directional migration of mesodermal cells (Nagel et al, 2004;Damm and Winklbauer, 2011). PDGF signaling also regulates cell polarization and the formation of cellular processes by mesendodermal cells in zebrafish, but apparently not their directional migration (Montero et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In both models, migrating mesendoderm cells orient their protrusions toward the direction of migration (Fig. 2 j; Davidson et al, 2002;Montero et al, 2003;Diz-Muñoz et al, 2010;Damm and Winklbauer, 2011;Dumortier et al, 2012;Weber et al, 2012). Similar to the neural crest, the Wnt/planar cell polarity (PCP) pathway has been suggested to contribute to orientation of protrusions and coordination of migration of mesendodermal cells (Ulrich et al, 2003;Dumortier et al, 2012).…”
Section: Polarization Of the Collective: Leaders And Followersmentioning
confidence: 98%
“…2 i) and to regulate directional migration of leading edge precursors in a PDG FR/PI3K-dependent manner (Nagel et al, 2004). A shorter, soluble one instead regulates protrusion orientation and directionality of migration of deep mesoderm prechordal cells (Damm and Winklbauer, 2011).…”
Section: The Role Of Chemotactic Cues In Guiding the Collectivementioning
confidence: 99%